Perubahan Sosial dan Modernisasi Dalam Pendidikan Era 5.0 - F, Firman; Maulana, Pu’ad; Sukma, Dina (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Education stems from human existence. And it is known that education contributes to the process of building society and achieving the pillars that support it. through the acquisition of cultural heritage and individuals Education leads to cultural socialization. Associated with social values and maintaining mutual relationships that determine the process of changing the socio-cultural structure of society and civilization. The writing of this article uses a qualitative approach with a descriptive analysis method that focuses on library research. Education is a conscious process carried out to pass on culture from one generation to the next. Education aims to develop a person's intellectual, moral and religious abilities. The educational process also plays an important role in socio-cultural change, modernization, and development in the 5.0 era.